Calcific Aortic Valve Disease-Natural History and Future Therapeutic Strategies - Alushi, Brunilda; Curini, Lavinia; Christopher, Mary Roxana; Grubitzch, Herko; Landmesser, Ulf; Amedei, Amedeo; Lauten, Alexander (Frontiers in Pharmacology, 2020)
Calcific aortic valve disease (CAVD) is the most frequent heart valve disorder. It is characterized by an active remodeling process accompanied with valve mineralization, that results in a progressive aortic valve narrowing, significant restriction of the valvular area and impairment of blood flow. The pathophysiology of CAVD is a multifaceted process, involving genetic factors, chronic inflammation, lipid deposition and valve mineralization. Mineralization is strictly related to the inflammatory process in which both, innate and adaptive immunity are involved. The underlying pathophysiological pathways that go from inflammation to calcification and, finally lead to severe stenosis, remain, however, incompletely understood. Histopathological studies are limited to patients with severe CAVD and no samples are available for longitudinal studies of disease progression. Therefore, alternative routes should be explored to investigate the pathogenesis and progression of CAVD. Recently, increasing evidence suggests that epigenetic markers such as non-coding RNAs are implicated in the landscape of phenotypical changes occurring in CAVD. Furthermore, the microbiome, an essential player in several diseases, including the cardiovascular ones, has recently been linked to the inflammation process occurring in CAVD. In the present review, we analyze and discuss the CAVD pathophysiology and future therapeutic strategies, focusing on the real and putative role of inflammation, calcification and microbiome.